Sistem Pengendali Penampungan Air dalam Rumah Tangga dengan Menggunakan Mikrokontroller AT89S51 - Abdurahman Abdurahman (Universitas Indraprasta PGRI Jakarta, 2018)
The automatic systems are now getting more popular. One of them is the filling system of water tank in our house. Even so, the current water tank runs automatically only for its filling system. It still uses manual system for its drainage system. In fact, the automatic filling and drainage water tank systems can be used to provide cleaner water that can be beneficial for health. The method used is looking at the working of water tank currently used to see the deficiencies in its automatic system. Then, designing and assembling a tool to get an expected result, namely the water tank system working automatically, both its filling system and drainage system. The design of this tool system uses LDR as input to run the microcontroller circuit to produce output.